2017
DOI: 10.1016/j.jcrs.2017.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular microbypass stent implantation with cataract extraction in pseudoexfoliation glaucoma

Abstract: Trabecular microbypass stent implantation during cataract surgery safely and effectively lowered IOP and medication use in patients with mild to severe PXG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 15 publications
6
22
0
1
Order By: Relevance
“…Although this is not a true “off label” use of the device, the clinical trials leading to its approval did not include eyes with pigmentary or pseudoexfoliative glaucoma. In addition, while not directly comparable, the results of this study are comparable or superior to our published data in eyes with POAG and PXG . At M24 postoperative in those studies, the mean IOP reduction in the POAG and PXG eyes was 3.96 and 5.49 mmHg, respectively.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although this is not a true “off label” use of the device, the clinical trials leading to its approval did not include eyes with pigmentary or pseudoexfoliative glaucoma. In addition, while not directly comparable, the results of this study are comparable or superior to our published data in eyes with POAG and PXG . At M24 postoperative in those studies, the mean IOP reduction in the POAG and PXG eyes was 3.96 and 5.49 mmHg, respectively.…”
Section: Discussionsupporting
confidence: 73%
“…There was a minimal rate of IOP spikes with only a single case of IOP increase ≥15 mmHg above baseline, no intra‐ or postoperative complications related to the procedure and no eyes required secondary surgery. These results, coupled with our results demonstrated in a pseudoexfoliative glaucoma (PXG) population, further support the device's utility may extend beyond eyes with primary open‐angle glaucoma (POAG). Although this is not a true “off label” use of the device, the clinical trials leading to its approval did not include eyes with pigmentary or pseudoexfoliative glaucoma.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Vorübergehende, meist selbstlimitierende Hyphämata sind die noch am meisten in der Literatur beschriebenen Komplikationen [9,34,36]. Sehr selten findet man postoperative IOD-Spitzen [10,14,30] und Stentobstruktionen oder -verlagerungen [8,31,36]…”
Section: Glaukomchirurgie Hat Zunehmend An Bedeutung Gewonnenunclassified